2020
DOI: 10.1186/s40657-020-00220-x
|View full text |Cite
|
Sign up to set email alerts
|

Potential cuckoo hosts have similar egg rejection rates to parasitized host species

Abstract: Background: Thrush species are rarely parasitized by cuckoos, but many have a strong egg recognition ability. To date, there is a limited understanding of the relationship between host egg rejection and cuckoo parasitism rate. Methods: By using egg experiments in the field, we compared egg rejection between two non-parasitized potential host species and two parasitized hosts of cuckoos in the same region. Results: The White-bellied Redstart (Luscinia phoenicuroides), a host of the Common Cuckoo (Cuculus canoru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
1
Order By: Relevance
“…Previous studies have shown that the degree of egg rejection by the host of cuckoos was significantly and positively correlated with the degree of parasitism rate (Røskaft et al, 2002), which was not supported by the results of the present study as all three bunting species had strong egg recognition but low cuckoo parasitism rates (for comparison, 9% in corn bunting, n = 90, Antonov et al, 2006;11.5% in Jankowski's bunting, n = 95, Zhang et al, 2020). Similarly, the findings of Yi et al (2020) showed no difference in egg recognition ability between potential hosts and currently used hosts. Since some host species have a strong ability to reject eggs in the absence of parasitism (Lahti, 2006;Medina & Langmore, 2015;Underwood et al, 2004), brood parasitism rates may not be a primary indicator of host egg recognition ability, or that they were once subjected to parasitism pressure and egg recognition ability is retained.…”
Section: Discussioncontrasting
confidence: 96%
See 4 more Smart Citations
“…Previous studies have shown that the degree of egg rejection by the host of cuckoos was significantly and positively correlated with the degree of parasitism rate (Røskaft et al, 2002), which was not supported by the results of the present study as all three bunting species had strong egg recognition but low cuckoo parasitism rates (for comparison, 9% in corn bunting, n = 90, Antonov et al, 2006;11.5% in Jankowski's bunting, n = 95, Zhang et al, 2020). Similarly, the findings of Yi et al (2020) showed no difference in egg recognition ability between potential hosts and currently used hosts. Since some host species have a strong ability to reject eggs in the absence of parasitism (Lahti, 2006;Medina & Langmore, 2015;Underwood et al, 2004), brood parasitism rates may not be a primary indicator of host egg recognition ability, or that they were once subjected to parasitism pressure and egg recognition ability is retained.…”
Section: Discussioncontrasting
confidence: 96%
“…Similarly, the findings of Yi et al. (2020) showed no difference in egg recognition ability between potential hosts and currently used hosts. Since some host species have a strong ability to reject eggs in the absence of parasitism (Lahti, 2006; Medina & Langmore, 2015; Underwood et al., 2004), brood parasitism rates may not be a primary indicator of host egg recognition ability, or that they were once subjected to parasitism pressure and egg recognition ability is retained.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations